TECHNOLOGY, PREVENTION AND CARE OF THE AFFECTED POPULATION IN THE EVENT OF NATURAL DISASTERS IN PERU - Cordova Krugg, Arístides Ivan (2022)
Natural events known as disasters arevery common in Peru; landslides, floods orLandslides have caused, for decades, manydrawbacks, leaving entire populations in theutter helplessness. However, and as a result of advances intechnological matter, these phenomena can not onlybe prevented, but come to be fully understood.On the other hand, technology plays an important role,since it alerts the population to take shelter; ifof the presence of tsunamis, technologies can warnfor the population to be safe. This article ofreflection aims to establish a dissertationaround natural disasters, as well as lookingnearby which technological devices can, somehowway, generate satisfactory responses in favor of lifeand, in this way, protect those vulnerable areas againstthese events, especially in affected populations.